1545 The Use of Drug Manipulation to Obtain Doses Required in Paediatric Practice: A Systematic Review. (October 2012) - Richey, RH; Craig, JV; Shah, UU; Ford, JL; Barker, CE; Peak, M; Nunn, AJ; Turner, MA
Abstract : Background and Aims: To determine whether there is an evidence base for drug manipulation to obtain the required dose, a common feature of paediatric clinical practice. Methods: Systematic review, including studies that considered the dose accuracy of manipulated medicines of any dosage form, evidence of safety or harm, bioavailability, patient experience, tolerability, contamination and comparison of methods of manipulation. Results: 43 studies were eligible for inclusion, 42 of which involved tablets being cut, split, crushed or dispersed. The remaining one study involved the manipulation of suppositories of one drug. No eligible studies concerning manipulation of oral capsules or liquids, rectal enemas, nebuliser solutions, injections or transdermal patches were identified. Seventeen of the tablet studies considered dose accuracy using weight and/or drug content. In studies that considered weight using adapted pharmacopoeial specifications, the percentage of halved tablets meeting these specifications ranged from 33% to 93%. Nine studies investigated bioavailability outcomes following the manipulations of five delayed release formulations. In all nine studies all of the dosage form was administered. Only one study was identified where drugs were manipulated to obtain a proportion of the dosage form, and that proportion administered. The eight studies that considered patient experience found that having to manipulate the tablets did not have a negative impact on adherence. Of the 43 studies only two studies reported investigating children. Conclusion: This review yielded limited evidence to support manipulation of medicines. The results cannot be extrapolated between dosage forms, methods of manipulation or between different brands of preparation.